Principles of Supply Chain Management, 5th Edition - Joel D. Wisner; Keah-Choon Tan; G. Keong Leong (Cengage Learning, 2018)
Examine the latest practices, trends, and emerging developments as PRINCIPLES OF SUPPLY CHAIN MANAGEMENT: A BALANCED APPROACH, 5E guides you step-by-step through the management of all supply chain activity. You review issues related to both domestic and global supply chains as comprehensive, one-of-a-kind coverage encompasses important processes in operations, purchasing, logistics, as well as process integration. A balanced approach follows the natural flow through the supply chain. Well-organized chapters demonstrate the practical applications of supply chain management in today's workplace with the help of intriguing SCM Profiles and interesting real business examples. Relevant end-of-chapter questions, problems, and new cases help you put what you learn into practice as you sharpen your management skills.